CCN Spectral Shape and Stratus Cloud and Drizzle Microphysics. Issue 17 (8th September 2018) - Hudson, James G.; Noble, Stephen; Tabor, Samantha
Abstract: The shapes of high‐resolution cloud condensation nucleus (CCN) spectra are compared with cloud and precipitation characteristics observed in the Marine Stratus/Stratocumulus Experiment. These high‐resolution spectra often revealed bimodality that is usually caused by in‐cloud processing. Bimodal CCN spectra were associated with clouds that had as much as double the concentrations of droplets with narrower distributions and as much as an order of magnitude less drizzle than clouds associated with the most extreme unimodal CCN spectra. We introduce objective CCN spectral metrics: (1) CCN concentration differences between the two modes, unprocessed (Aitken, N u ) and processed (accumulation, N p ), and (2) slopes of cumulative CCN spectra. Both of these CCN spectral shape classifications show similar cloud droplet concentration ( N c ) trends to that of an earlier subjective modal rating system. When there are two modes, they are separated either by minimal concentrations or concentration inflections. Enhancement of N c is traced to greater CCN bimodality that causes narrower droplet spectra that suppress drizzle. These effects could augment indirect aerosol effects and can only be revealed by high‐resolution CCN spectral shape comparisons with cloud and drizzle microphysics. Plain Language Summary: Bimodal cloud condensation nuclei suppressed drizzle in the stratus clouds of the Marine Stratus/Stratocumulus Experiment project. Key Points: Bimodal CCN affects cloud microphysics in stratus Normalized concentration difference between modes (ndf) is a more objective classification metric for CCN modality Bimodal CCN suppresses drizzle in stratus